A Pragmatic Analysis of Speech Acts Used by English Lecturers in Languange Teaching at STKIP YDB Lubuk Alung - Siska Okta Widya (Masyarakat Linguistik Indonesia Universitas Andalas, 2017)
The research was intended to describe types of speech acts performed by English lecturers in learning process at STKIP YDB Lubuk Alung. This research was descriptive qualitative. The data of this research were the English utterances performed by English lecturers. The researcher obtained the data by means of note-taking technique. First, the researcher recorded the English teaching in the class using a video camera. Next, the researcher made transcripts of the dialogues. Then, the transcribed dialogues were recorded into the data sheet. Finally the data were classified according to Searle's classification of speech acts. In the data analysis the researcher applied interactive qualitative method and applied coding system. The research findings show that there were four types of speech acts performed by the English lecturers, namely representatives, directives, expressive and commissives, whereas declarations were not utilized by the English lecturer. The most frequently used illocutionary acts were directives (53%), while the least frequent illocutionary acts went to commissives (5%). The frequent use of directives indicates that the lecturer seemed to be aware of their status as a lecturer which was believed to be more powerful than her students. In such restricted context like classroom setting, it is common that the lecturer status is higher than her students since the relation between them is inherently asymmetrical. It was through directives the lecturers exerted her power over the students.